2015
DOI: 10.3892/ol.2015.2966
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient radiofrequency ablation promotes human hepatoma SMMC7721 cell proliferation by stimulating vascular endothelial growth factor overexpression

Abstract: The aims of the current study were to investigate the influence of insufficient radiofrequency ablation (RFA) on the cell proliferation of the human hepatocellular carcinoma (HCC) cells, SMMC7721, and to elucidate the underlying mechanism. SMMC7721 cells were subjected to a 47°C treatment regimen to simulate insufficient RFA, in the presence or absence of KN93 [a specific inhibitor of Ca2+/calmodulin-dependent protein kinase II (CaMKII)], PD98059 [a specific inhibitor of extracellular signal-regulated kinase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 19 publications
(25 reference statements)
0
29
1
Order By: Relevance
“…However, one of the major challenges associated with RFA is the rapid growth of residual HCC, thus leading to high recurrence rates associated with the cancer (6,8). As reported, post-RFA local recurrence rates can reach up to 60% (14).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…However, one of the major challenges associated with RFA is the rapid growth of residual HCC, thus leading to high recurrence rates associated with the cancer (6,8). As reported, post-RFA local recurrence rates can reach up to 60% (14).…”
Section: Discussionmentioning
confidence: 92%
“…Our previous study demonstrated that CaMKII/ERK-dependent VEGF overexpression was involved in the 47˚C treatment-induced malignant proliferation of SMMC7721 cells (6). Thus, the present study further investigated the association between EGFR transactivation and the CaMKII/ERK/VEGF signaling cascade.…”
Section: Ag1478 Significantly Inhibits Rfa-induced Overexpression Of mentioning
confidence: 97%
See 3 more Smart Citations